Electrifying White Biotechnology: Engineering and Economic Potential of Electricity‐Driven Bio‐Production. Issue 5 (20th February 2015) - Harnisch, Falk; Rosa, Luis F. M.; Kracke, Frauke; Virdis, Bernardino; Krömer, Jens O.
Abstract Invited for the cover of this issue are the groups of Falk Harnisch at the Helmholtz Centre for Environmental Research (Germany) and his collaboration partners at The University of Queensland (Australia). The image depicts their vision of the world, if "electrification" of white biotechnology comes true. The Concept itself is available at 10.1002/cssc.201402736.